2006
DOI: 10.1261/rna.136206
|View full text |Cite
|
Sign up to set email alerts
|

The disparate nature of “intergenic” polyadenylation sites

Abstract: The termination of mature eukaryotic mRNAs occurs at specific polyadenylation sites located downstream from stop codons in the 39-untranslated region (UTR). An accurate delineation of these sites is essential for the study of 39-UTR-based gene regulation and for the design of pertinent probes for transcriptome analysis. Although typical poly(A) sites are located between 0 and 2 kb from the stop codon, EST sequence analyses have identified sites located at unexpectedly long ranges (5-10 kb) in a number of genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 34 publications
4
25
0
Order By: Relevance
“…While their authenticity as potentially unannotated gene transcripts remains to be tested, their existence at such a scale (∼23%) requires further investigation. Similarly, previous studies also showed that there were many poly(A) sites in the intergenic regions (Lopez et al 2006;Shepard et al 2011;Derti et al 2012). Concerning the rice data presented herein, additional evidence implies that these are authentic poly(A) sites.…”
Section: Discussionsupporting
confidence: 88%
“…While their authenticity as potentially unannotated gene transcripts remains to be tested, their existence at such a scale (∼23%) requires further investigation. Similarly, previous studies also showed that there were many poly(A) sites in the intergenic regions (Lopez et al 2006;Shepard et al 2011;Derti et al 2012). Concerning the rice data presented herein, additional evidence implies that these are authentic poly(A) sites.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, these sequences cannot fully account for the specificity of 3Ј-end processing. Putative poly(A) signals are frequently found within AU-rich sequences, such as introns and intergenic regions (21,37). In addition, bioinformatical studies have determined that the sequence motifs that make the poly(A) signal are, contrary to earlier predictions, not well conserved, even in mammalian genes.…”
mentioning
confidence: 92%
“…The prediction tables are based on methodology that improves on earlier EST-based analyses (14)(15)(16)(17)(18)(19) and demonstrates a 97% level of predictive recall on a hand-curated and experimentally supported benchmark transcript set. Exact and comprehensive definition of alternative 3Ј transcript ends will allow for the design of probes that discriminate between alternative forms and thereby support elucidation of the regulatory impact of alternative polyadenylation.…”
Section: Discussionmentioning
confidence: 99%